Hubungan Motivasi Belajar Dengan Prestasi Belajar Siswa - Markus Arkian Terong; Matilda Pia Bone; Rosa Mustika Bulor (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2024)
The focus of this research is to see whether there is a relationship between learning motivation and learning achievement students. This study aimed to investigate the significant relationship between learning motivation and learning achievement of eight grade students at SMP Negeri 16 Kupang in the academic year of 2023/2024. This study belonged to quantitative descriptive method. The variables of this study were independent variable (X) learning motivation and dependent variable (Y) learning achievement. The population was all students in class A of eight graders at SMP Negeri 16 Kupang in the academic year of 2023/2024. 23 students were chosen as the sample of this research. The data collection technique used in this study was a questionnaire. The product moment correlation was used as the data analysis technique in this study. The results of data analysis showed a value of Pearson Correlation was 0.575 with a significance value obtained of 0.00 <0.05, including the strong category. The finding showed that there was a significant relationship between learning motivation and the learning achievement in class A of eight graders at SMP Negeri 16 Kupang in the academic year of 2023/2024.